2016
DOI: 10.1007/s11240-016-1022-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of virus-induced gene silencing approach in Camptotheca acuminata

Abstract: Camptotheca acuminata is the major plant for the production of camptothecin (CPT), an important anticancer drug used for the treatment of various cancers throughout the world. The low accumulation of CPT in plants limited its supply in the market and led to urgent need of promoting its accumulation by means of plant metabolic engineering, which relied on deep understanding of CPT biosynthesis pathway. However, missing of most of pathway genes restricted the attempts for regulating CPT biosynthesis. To unveil t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…As shown in Figure 1 , in the MAE method, when aqueous acetonitrile of 70% was used as the extraction solvent, the recoveries of the three target compounds ranged between 88% and 103%, and acetonitrile had the highest extraction efficiency for two of the key intermediates (loganic acid, strictosamide). The most commonly employed solvent for the extraction of CPT and 10-HCPT in plant samples is methanol [ 8 , 13 , 17 ]. However, fewer systematic studies on intermediates extraction were reported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Figure 1 , in the MAE method, when aqueous acetonitrile of 70% was used as the extraction solvent, the recoveries of the three target compounds ranged between 88% and 103%, and acetonitrile had the highest extraction efficiency for two of the key intermediates (loganic acid, strictosamide). The most commonly employed solvent for the extraction of CPT and 10-HCPT in plant samples is methanol [ 8 , 13 , 17 ]. However, fewer systematic studies on intermediates extraction were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Seed germination and plant growth were conducted as described by Jin et al [ 8 ]. Briefly, seeds were germinated on wet filter paper in a growth chamber with a 12 h photoperiod at 25 °C until cotyledons appeared.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations